Improvement of macular edema without discontinuation of fingolimod in a patient with multiple sclerosis: A case report. Issue 29 (July 2016) - Akiyama, Hisanao; Suzuki, Yu; Hara, Daisuke; Shinohara, Kensuke; Ogura, Hana; Akamatsu, Masashi; Hasegawa, Yasuhiro
Abstract: Introduction: Generally, fingolimod administration is simply discontinued when fingolimod-associated macular edema (ME) appears, and the majority of cases are said to recover spontaneously. However, to the best of our knowledge, this is the 1st report regarding improvement of ME without discontinuation of fingolimod administration. Case presentation: The patient was a 66-year-old woman with relapsing-remitting multiple sclerosis. She was started on treatment with fingolimod to prevent recurrence, after which she developed ME that was probably due to fingolimod. The patient expressed a strong fear of recurrence if fingolimod was discontinued, so we continued fingolimod therapy and followed up the patient frequently. The ME improved after approximately 1 year without any need for concomitant treatment. Conclusion: We believe that the continuation of fingolimod therapy with strict follow-up examination is one option for treatment, though strategies for managing rapid deterioration of ME should be borne in mind.